Pendidikan Kesehatan Menggunakan Audiovisual Terhadap Tingkat Pengetahuan Tentang Pemeriksaan Payudara Sendiri (SADARI) - Marsanti, Francisca Devysintia Rintan; Setyani, Fransisca Anjar Rina; Rahayu, Margareta Hesti (I Care Jurnal Keperawatan STIKes Panti Rapih, 2023)
Background: The high mortality rate due to breast cancer who come to health services is at an advanced stage, because patients do not know about breast cancer such as risk factors, signs and symptoms and how to detect cancer early, in Indonesia, more than 80% of cases are found are in an advanced stage, where treatment efforts are difficult to do.Purpose: The purpose of this study was to determine the effect of health education about BSE with audiovisual for class XII students at SMK Jogonalan Klaten.Methods: This study used a pre-experimental design with a one-group pre-test-post-test design approach. The sample in this study was obtained by 72 respondents obtained by accidental sampling technique.Results: The results of data analysis using the Wilcoxone test obtained p value = 0.000 (p <0.005) meaning that there was a significant difference in the level of knowledge of female students before and after being given health education using audiovisual about BSE.Conclusion: The results of the characteristics of the study showed that most of the respondents were 17 years old (66%), based on the characteristics of a family history of breast cancer, there were 70 people (97.2%), then the third characteristic, namely sources of information about BSE, were 67 people with a proportion of 93.1%. The results of research that has been conducted on the effect of health education using audiovisual on the level of knowledge of class XII students at Jogonalan Vocational School in self-breast examination (BSE) shows that the knowledge of students before being given health education is in the sufficient category, a large proportion of 38.9% and after being given health education some the majority of respondents have knowledge in the good category with a proportion of 87.5%.